2021
DOI: 10.1002/2211-5463.13204
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in circulating extracellular vesicles underlie social stress‐induced behaviors in mice

Abstract: Chronic stress induces peripheral and intracerebral immune changes and inflammation, contributing to neuropathology and behavioral abnormalities relevant to psychiatric disorders such as depression.Although the pathological implication of many peripheral factors such as pro-inflammatory cytokines, hormones, and macrophages has been demonstrated, the roles of circulating extracellular vesicles (EVs) for chronic stress mechanisms remain poorly investigated. Here we report that chronic social defeat stress (CSDS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Our studies indicate a central role of phosphatidic acid as effector of exosomal ceramide in the blood plasma in the pathogenesis of MDD. However, exosomes have been shown to also contain miRNA molecules that can be altered under stress [ 46 ]. Furthermore, several miRNA molecules, for instance miR-34a, miR-106, miR-134, and miR-132, are deregulated in MDD and show brain enrichment in MDD [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our studies indicate a central role of phosphatidic acid as effector of exosomal ceramide in the blood plasma in the pathogenesis of MDD. However, exosomes have been shown to also contain miRNA molecules that can be altered under stress [ 46 ]. Furthermore, several miRNA molecules, for instance miR-34a, miR-106, miR-134, and miR-132, are deregulated in MDD and show brain enrichment in MDD [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…SIT was performed to evaluate social avoidance, which belongs to social processes, a domain relevant to the psychopathology of depression ( Carcone and Ruocco, 2017 ). As we previously described ( Zhu et al, 2019 ; Sakamoto et al, 2021 ), mice were placed in a three-chamber apparatus (40 cm width × 20 cm height × 26 cm depth) containing a small, porous cage in the corner of each side chamber. Each trial consisted of 3 sessions: 1) The mouse was placed in the center chamber to habituate for 10 min, 2) the mouse was allowed to freely explore the empty side-chambers for an additional 10 min, and 3) a stranger mouse (stranger) of the same strain was placed in the plastic cage in one chamber, while a novel inanimate object (object) was placed in the opposing chamber's cage, and the test mouse was again allowed to explore all chambers freely for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Sakamoto et al [380] showed that plasma EVs from CSDS-susceptible mice with a social avoidance phenotype had a distinct miRNA profile, which distinguished them from CSDS-resilient mice. Among the differentially expressed miRNAs, miR-31-5p, miR-712-5p, miR-212-3p, miR-451a, miR-467b-3p, miR-193b-3p and miR-93-5p were associated with inflammation.…”
Section: Evs In Animal Models Of Stressmentioning
confidence: 99%